Assessing the welfare of pasture-based dairy cows of New Zealand and transhumance chauris of Nepal : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Runenga Porehuroa, University of New Zealand, School of Veterinary Science, Manawatu - Sapkota, Sujan (Massey University, 2024)
There is no industry-recognized welfare assessment protocol for pasture-based dairy cows of New Zealand. Also, the welfare assessment in yak/chauri raised under the transhumance system is at the preliminary stage. So, there is a strong necessity of a pastured-based welfare assessment protocol for pasture-based dairy cows in New Zealand and transhumance yak/chauri in Nepal. The aim of the research studies presented in this thesis were to develop a practical and time-limited welfare assessment protocol suitable to pasture-based dairy farms, and transhumance yak chauri focused on a single visit around milking. During the process, 84 different welfare measures were collected from six protocols and 4 welfare studies which were screened and trialed in two pasture-based farms to finalise 32 welfare measures including 5 additional measures specific to New Zealand. These measures were tested on 23 different dairy farms from the Waikato and Manawatu. All the measures were feasible except for the measure related to water availability and behavior. Testing of the repeatability and reliability should be performed for all the selected measures on more number of farms before taking this protocol for commercial use. Also, we further did subsampling-based locomotion scoring on five different pasture-based dairy farms to know if they could predict herd level prevalence. The findings were that there was a significant association between the order in which cows were milked and their susceptibility to lameness. However, the percentage of lame cows within the sub-sampled group was not uniform and was significantly influenced by the farm and the timing of the visit. For our yak/chauri protocol, 31 potential welfare measures were submitted to 120 Nepalese experts for evaluation identifying 13 measures, plus a new one (hematology) was deemed useful. The resulting protocol was tested in five chauri herds in northern Nepal, encompassing animal-based evaluations, mastitis and parasite sampling, and hematology. The protocol was found to be feasible and offers a valuable starting point for yak/chauri welfare assessment.
Keywords: Animal welfare; Animal health surveillance; Dairy cattle; Health; Condition scoring; New Zealand; Yak; Reproduction; Climatic factors; Nepal; pasture-based dairy cows; yak hybrids; welfare assessment; 300306 Animal welfare; 300999 Veterinary sciences not elsewhere classified